Linezolid in the Starter Combination for Multidrug-Resistant Tuberculosis: Time to Move on to Group Four?. (22nd December 2015) - Grard, Soazic; Catho, Gaud; Valour, Florent; Bouaziz, Anissa; Perpoint, Thomas; Braun, Evelyne; Biron, François; Miailhes, Patrick; Ferry, Tristan; Chidiac, Christian; Souquet, Pierre-Jean; Couraud, Sébastien; et al.
Abstract: Linezolid (LNZ), a group 5 antituberculous drug (unclear efficacy), was used in the starter regimens of 23 adults with multidrug-resistant tuberculosis. The LNZ-containing regimens were effective in achieving culture conversions and relapse-free outcomes. The most frequent LNZ-related side effect was neuropathy. We propose that LNZ should be reclassified among bactericidal second-line drugs.